THE LEGAL POSITION OF CANING PUNISHMENT IN ACEH - Zulfan Zulfan; Muhammad Hatta (International Journal of Law, Environment, and Natural Resources, 2021)
Amongst the punishments that have been implemented in the Islamic criminal law is caning punishment. The caning punishment in Aceh is carried out directly and opens to the public. However, some Islamic countries carry out caning in private such as in prisons. In Aceh, the implementation of caning that has been carried out openly is based on Aceh Qanun Number 6 of 2014 concerning Jinayat Law and Qanun No. 7 of 2013 concerning Jinayat Procedural Law. However, in 2015, the implementation of the caning was carried out behind closed doors like in prisons. This is in accordance with the Governor Regulation Number 5 of 2018 about the Implementation of 'Uqubat Whip’ in the Correctional Institutions. Changes in the implementation of the caning punishment led to the pros and cons among the society. Many believe that the implementation of caning in a closed manner will affect the effectiveness of the punishment in reducing the number of shari'ah violations. Although there are many factors that influence the number of crime in society, the punishment and the implementation of the punishment itself are considered as the most important factors